Estrogen Receptor α (ERα)-targeting Compounds and Derivatives: Recent Advances in Structural Modification and Bioactivity - Guo, Wei-Yun; Zeng, Shang-Ming-Zhu; Deora, Girdhar S.; Li, Qing-Shan; Ruan, Ban-Feng (Current Topics in Medicinal Chemistry, 2019)
Breast cancer is the most common cancer suffered by female, and the second highest cause of cancer-related death among women worldwide. At present, hormone therapy is still the main treatment route and can be divided into three main categories: selective estrogen receptor modulators (SERMs), selective estrogen receptor downregulators (SERDs), and aromatase inhibitors (AIs). However, breast cancer is difficult to cure even after several rounds of anti-estrogen therapy and most drugs have serious side-effects. Here, we review the literature published over the past five years regarding the isolation and synthesis of analogs and their derivatives.
Keywords: Estrogen receptor α